The hydrogen dependent CO2 reductase: the first completely CO tolerant FeFe-hydrogenase. Issue 2 (2nd November 2016) - Ceccaldi, Pierre; Schuchmann, Kai; Müller, Volker; Elliott, Sean J.
Abstract : The Hydrogen Dependent Carbon dioxide Reductase (HDCR) from Acetobacterium woodii presents a promising solution to the issue of H2 storage by reversibly coupling H2 oxidation to CO2 reduction. Abstract : The Hydrogen Dependent Carbon dioxide Reductase (HDCR) from Acetobacterium woodii presents a promising solution to the issue of H2 storage by reversibly coupling H2 oxidation to CO2 reduction. We here report on the electrocatalytic properties of the hydrogenase (Hase) module in the intact complex, including (an)aerobic oxidation, CO inhibition and the first systematic analysis of the catalytic bias (CB) of a Hase. CB depends on pH, regardless of the H2 concentration, despite a higher affinity for H2 than other FeFe-Hases. Remarkably, CO inhibition is fully reversible under all oxidation states of the active site, making HDCR the first "syngas-friendly" FeFe-Hase.